Inhomogenous risk exposure in dual insurance system: selection effects in Germany's long-term care plans - Thomas Neusius (SN Business & Economics, 2021)
Long-term care (LTC) gains attention in ageing societies. Making LTC insurance affordable for the wide public is a primary objective of politics and insurance companies alike. Germany's LTC insurance, introduced 25 years ago, is split in two branches, a private and a public one. The per-capita claims diverge in the two systems. This study is dedicated to explain the difference in average claims seen in the German LTC system. Based on publicly available claims data, we decompose the contributions to the difference in claims and we quantify the advantage gained by the private LTC insurance through selection of low-risk enrollees. Furthermore, the study provides simulation results of the development of the claims' differences over the next 40 years. In order to level off the claims differences, transfer payments from the private to the public LTC insurance have been suggested as a matter of fair risk sharing. However, it turns out that such a payment scheme does not necessarily work in favor of the public system troughout the next 40 years. Therefore, it seems unlikely that such a financial transfer is able to substantially ease the public LTC insurance's financial burden.
Keywords: G22; I13; I18; 330; Long-term care; Health insurance; Risk adjustment; Pay-as-you-go system